Enhanced osteoinductivity and osteoconductivity through hydroxyapatite coating of silk‐based tissue‐engineered ligament scaffold 1. Issue 2 (4th September 2012) - He, Pengfei; Sahoo, Sambit; Ng, Kian Siang; Chen, Kelei; Toh, Siew Lok; Goh, James Cho Hong
Abstract: Hybrid silk scaffolds combining knitted silk fibers and silk sponge have been recently developed for use as ligament‐alone grafts. Incorporating an osteoinductive phase into the ends of a ligament scaffold may potentially generate an integrated "bone–ligament–bone" graft and improve graft osteointegration with host bone. To explore the possible application of hydroxyapatite (HA) coating in the fabrication of osteoinductive ends of silk‐based scaffold, HA was coated on the hybrid silk scaffold and the effects to the bone‐related cells were evaluated. HA could be coated in a uniform and controlled manner on the silk sponge, using an alternate soaking technology, with the amount deposited being dependent on the number of soaking cycles. HA coating also progressively reduced the hydrophobicity of silk surface (decreasing water contact angle from 87° to 42–76°, after 1–3 soaking cycles), making the HA‐coated silk scaffold less favorable for initial cell attachments; but the attached cells showed viability and sustained proliferation on the HA‐coated scaffold. As demonstrated by real‐time polymerase chain reaction and alkaline phosphatase assay, the osteoinductivity of HA‐coated silk scaffolds resulted in the osteogenic differentiation of bone marrow mesenchymal stem cells, and the osteoconductivity of HA‐coated silk scaffolds supported osteoblasts growth and maintained the properties of mature osteoblasts. These properties of HA‐coating demonstrated its possible application in fabricating osteoinductive ends of the silk‐based ligament graft to potentially enhance graft‐to‐host bone integration. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.